2013
DOI: 10.1097/pai.0b013e318261a342
|View full text |Cite
|
Sign up to set email alerts
|

CD123 Immunohistochemical Expression in Acute Myeloid Leukemia is Associated With Underlying FLT3-ITD and NPM1 Mutations

Abstract: FLT3-ITD and NPM1 mutation testing in acute myeloid leukemia (AML) plays an important role in prognostic risk stratification, especially within the intermediate cytogenetic risk group. Molecular studies require adequate fresh material and are typically performed on a dedicated aspirate specimen, which may not be available in all cases. Prior flow cytometric studies have suggested an association between CD123 overexpression in AML and FLT3-ITD and/or NPM1 mutations; however, the immunohistochemical (IHC) correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 23 publications
4
15
0
Order By: Relevance
“…Rollins-Raval and colleagues (33) described the association of CD123 in AML patients with both FLT3 and NPM1 mutations, in keeping with our observations. Moreover, we reported a higher CD123 expression in FLT3 mutated AML patients as compared with those with germline FLT3 (16).…”
Section: Discussionsupporting
confidence: 81%
“…Rollins-Raval and colleagues (33) described the association of CD123 in AML patients with both FLT3 and NPM1 mutations, in keeping with our observations. Moreover, we reported a higher CD123 expression in FLT3 mutated AML patients as compared with those with germline FLT3 (16).…”
Section: Discussionsupporting
confidence: 81%
“…The result turned out that the proportion of CD34 + cells and CD34 + CD38 -cells in the observation group was significantly larger than the control group (P < 0.05). This result was consistent with the findings of Rollins-Raval [11]. It indicated that CD34 + abnormally differentiated in patients with MDS and it was correlated with the risk.…”
Section: Cd38supporting
confidence: 82%
“…Furthermore, in these AMLs the high CD123 expression is associated with IL-3R βc (CDw131) and GM-CSFRα (CD116) expression, thus supporting the notion that the majority of these AMLs display the concomitant overexpression of both IL3R and GM-CSFR [62]. Other studies have confirmed that CD123 overexpression in AMLs is associated with some peculiar molecular subtypes: CD123 overexpression was observed in 83% of FLT3-ITD-mutated AMLs and in 62% of AMLs with nucleophosmin 1 mutations [63]; AMLs characterized by CD25 positivity and poor prognosis display CD123 overexpression [64].…”
Section: Cd123 (Il3rα)mentioning
confidence: 79%
“…Concerning the first type of strategy, a genetically engineered fusion toxin composed of the first 388 amino acid residues of diphtheria toxin (DT) was fused to human IL3 [DT388IL3]: this fusion protein was shown to be toxic for leukemic blasts [74], the sensitivity of these cells being correlated with the level of IL3R receptor expressed on their membrane [75][76][77] and, particularly, for leukemic stem cells [63]. DT388IL3 was well tolerated in vivo up to 100 μg/kg [78].…”
Section: Cd123 (Il3rα)mentioning
confidence: 99%